The Predictive Role of L1 Pragmatics in L2 Implicature Comprehension: A Mediation Analysis - Pratama, Hendi (Journal of English Teaching and Learning Issues, 2025)
This study explores the role of first language (L1) pragmatic competence in second language (L2) conversational implicature comprehension among Indonesian EFL learners. Using a quantitative design with 103 university students, the research tested a model where L2 grammatical and lexical competence mediate the relationship between L1 and L2 implicature comprehension. The instruments used included a 30-item L2 implicature comprehension test, an L1 implicature comprehension test, a vocabulary knowledge test, a grammar knowledge test, and a self-report L2 exposure questionnaire. Results showed that L2 grammar proficiency was the strongest predictor of L2 implicature comprehension (r=.695). Mediation analysis confirmed a significant direct effect of L1 implicature comprehension on L2 comprehension, with an indirect effect of L2 grammar (p=.020). However, the mediating role of vocabulary was not significant. These findings suggest that L1 pragmatic knowledge is channeled through L2 grammatical proficiency to interpret implied meanings. The study underscores the significance of integrating grammar and pragmatics in instruction, recommending that educators link syntactic structures to their pragmatic functions to help learners leverage their L1 pragmatic intuition and improve L2 competence.